Effect of the openings on the seismic response of an infilled reinforced concrete structure - Furtado, André (2022)
The seismic behavior of the infill masonry infill walls has a significant impact on the global response of reinforced concrete frame structures. One factor influencing its behavior is the existence of openings in the walls, such as doors and windows, which are crucial for the infill seismic performance. Although the numerical simulation of the seismic behavior of RC buildings with infill walls has evolved significantly in recent years in terms of micro- and macro-modelling, most of the existing studies are only related to infill walls without openings. Based on this motivation, four main objectives were defined for this research work: (i) present a simplified modeling approach and its calibration to simulate the seismic behavior of infill walls with central openings such as windows; (ii) evaluate the impact of the openings on the global seismic response of an RC building; (iii) study the impact of the irregular distribution of the infill walls (vertical and in-plane) on the global seismic response of an RC building; and (iv) study the impact of the central openings ratio (i.e., relative percentage between opening and infill wall area) on the global seismic response of an RC building structure. A four-story infilled RC building was used as a case study to perform parametric analyses investigating the impact of the masonry infill walls’ irregular distribution (vertical and in-plan) and their openings ratio. The results are discussed in terms of natural frequencies and vibration modes, initial lateral stiffness, and maximum lateral resistance. This study found that the openings caused a reduction in the natural frequencies of about 20% compared with the full infill (without openings). The openings did not modify the vibration modes. In addition, the openings reduced the initial stiffness by about 20% compared with the model without openings. The maximum strength increased about 50% with the infill walls, but this was reduced by the openings by 20%.